Influence of reaction time on optical property of ZnS:Mn nanoparticles synthesized by a hydrothermal method - Pham, Van Ben (H. : ĐHQGHN, 2017)
ZnS:Mn (CMn = 5 %mol) nanoparticles have been synthesized by a hydrothermal method from solutions of Zn(CH3COO)2 0.1 M, Na2S2O3 0.1 M and Mn(CH3COO)2 0.01 M at 220oC for different reaction time. The result showed that increasing reaction time from 3 to 30h almost does not change cubic crystalline structure, peak positions attributed to Mn2+ ions at 585 nm in photoluminescence spectra and 392, 430, 463, 468, 492 nm in photoluminescence excitation spectra when monitoring the 585 nm band of ZnS:Mn nanoparticles but only slight increases lattice constant, the average particle size and changing their intensity. As increasing the reaction time from 3 to 10h, intensity of bands attributed to Mn2+ ions also increase, reaches the maximum at 15h and then decreases as increasing reaction time to 30 h. Cause of these phenomena have been investigated and reported.